KESADARAN, ASOSIASI, PERSEPSI KUALITAS, LOYALITAS MEREK DAN KEPUTUSAN PEMBELIAN KOPI TUBRUK GADJAH - Febrian Syah Saputra; Rohmat Riyadi, Muhammad Ilyas Al-Fazri, Handy Yustianto, Jeanica Irianti Sibarani, Riza Fahlapi (Jurnal Ekonomi dan Bisnis, 2024)
This research aims to investigate the impact of brand awareness, brand association, quality perception, and brand loyalty on consumer purchasing decisions, with a special focus on Kopi Tubruk Gadjah. The study aims to contribute to marketing theory and practice, providing insights for marketers and enriching general marketing knowledge. This document covers theoretical foundations of branding, brand equity, and brand strategies, as well as research methodology, data collection and analysis techniques, company profiles, and characteristics of respondents involved in the study.